CHINAT-CD4 Score Predicts Transplant-Free Survival in Patients with Acute-on-Chronic Liver Failure - Huang C; Li W; Chen C; Xu W; Fei L; Tao S; Hu Q; Xie X; Cao X; Zhang XY; Chen L; Li Q; et al. (Dove Medical Press, 2023)
Chenlu Huang,1,* Weixia Li,2,* Chong Chen,2,* Wei Xu,1 Ling Fei,1 Shuai Tao,3 Qiankun Hu,1 Xudong Xie,1 Xiongyue Cao,1 Xiao-Yu Zhang,1,4 Liang Chen,1 Qiang Li,1 Yuxian Huang1 1Department of Liver Disease, Shanghai Public Health Clinical Center, Fudan University, Shanghai, People's Republic of China; 2Department of Infectious Disease, Shanghai Public Health Clinical Center, Fudan University, Shanghai, People's Republic of China; 3Research Unit, Shanghai Public Health Clinical Center, Fudan University, Shanghai, People's Republic of China; 4Section of Education, Shanghai Public Health Clinical Center, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuxian Huang; Qiang Li, Email yxhuang@fudan.edu.cn; liqiang66601@163.comAim: The early prognosis evaluation of acute-on-chronic liver failure (ACLF) is important to decrease its mortality. We aimed to develop a new score to accurately predict the outcome of patients with ACLF.Methods: A derivation set of 408 patients with hepatitis B virus-related ACLF (HBV-ACLF) based on the Asian Pacific Association for the Study of the Liver criteria is used to develop a prognostic score that was validated in 209 patients with HBV-ACLF and 195 patients with non-HBV-ACLF.Results: Seven factors were significantly related to the 28-day mortality and constituted a new score (CHINAT-CD4 = 0.320 × ln (creatinine) + 0.668 × hepatic encephalopathy score + 0.745 × ln (international normalized ratio) + 0.476 × ln (neutrophil) + 0.251 × ln (aspartate aminotransferase) + 0.411 × ln (total bilirubin) - 0.605 × ln (CD4+ T cells count)). The C-indices of the new score for the 28-/90-day mortality (0.810/0.806) outperformed those of the other seven scores (p≤ 0.05). The results were confirmed in a validation set (0.798/793 for HBV-ACLF; 0.790/0.788 for non-HBV-ACLF). The novel score based on CD4+ T cell count showed high predictive performance for the 28-/90-day mortality of ACLF.Conclusion: The novel score based on CD4+ T cell count can accurately predict the 28-/90-day mortality for patients with ACLF.Keywords: liver failure, chronic liver disease, prognostic score, risk stratification, inflammatory markers